Integrating English Skills Competitions into the Curriculum and Students' Oral English Abilities - Du Ruixue; Princess Policarpio (International Journal of Education and Humanities, 2024)
This study investigates the integration of Skills Competitions and Oral English Expression Abilities among Liaocheng Vocational and Technical College, Shandong, China students. The primary issue addressed is the level of integration of English skills competitions into the curriculum and its impact on students' oral English expression abilities. This research aims to evaluate the extent to which English skills competitions have been incorporated into the learning process and to explore the relationship between the level of integration and students' oral English expression abilities. The study employed a descriptive-correlational research design, utilizing a survey questionnaire to collect student data. Descriptive statistics and correlation analysis were conducted to analyze the collected data. The findings indicate that integrating English skills competitions into the curriculum can significantly enhance students' oral English expression abilities, particularly in idiomatic usage and overall communicative competence. The positive impact largely depends on careful implementation that balances competitive activities with other pedagogical methods. The study recommends that educators ensure these competitions are designed to be inclusive and are part of a broader, well-rounded approach to language learning. In this way, English skills competitions can effectively improve students' oral language abilities, provided they are balanced and aligned with comprehensive pedagogical approaches